Structure of the ordered hydration of amino acids in proteins: analysis of crystal structures - Biedermannová, Lada; Schneider, Bohdan (Acta crystallographica. Section D, Biological crystallography, 2015)
Crystallography provides unique information about the arrangement of water molecules near protein surfaces. Using a nonredundant set of 2818 protein crystal structures with a resolution of better than 1.8 Å, the extent and structure of the hydration shell of all 20 standard amino-acid residues were analyzed as function of the residue conformation, secondary structure and solvent accessibility. The results show how hydration depends on the amino-acid conformation and the environment in which it occurs. After conformational clustering of individual residues, the density distribution of water molecules was compiled and the preferred hydration sites were determined as maxima in the pseudo-electron-density representation of water distributions. Many hydration sites interact with both main-chain and side-chain amino-acid atoms, and several occurrences of hydration sites with less canonical contacts, such as carbon-donor hydrogen bonds, OH-π interactions and off-plane interactions with aromatic heteroatoms, are also reported. Information about the location and relative importance of the empirically determined preferred hydration sites in proteins has applications in improving the current methods of hydration-site prediction in molecular replacement, ab initio protein structure prediction and the set-up of molecular-dynamics simulations.
Keywords: Water; lidé; Databases, Protein; Amino Acids; databáze proteinů; voda; Molecular Conformation; X-ray crystallography; protein hydration; aminokyseliny; vodíková vazba; Humans; Hydrogen Bonding; proteiny; sekundární struktura proteinů; structural biology; zvířata; krystalografie rentgenová; Protein Structure, Secondary; Animals; Crystallography, X-Ray; Proteins; molekulární modely; Models, Molecular; molekulární konformace